Effect of Synthesis Temperature on the Structure and Luminescence Properties of the NaAlSiO4:Er3+ Phosphors. (18th October 2021) - Mo, Zhurong; Huo, Yanping; Wu, Haoyi; Mohan, Brij; Wen, Hongli; Luo, Li; Hakeem, Deshmukh Abdul
Abstract : We report the synthesis and the effect of synthesis temperature on the crystal structure and dual mode (DC/UC) luminescence properties of the NASE-1000–1300. Two different polymorphs, i.e., nepheline and carnegieite of the NASE have been prepared just by changing the annealing temperature. Multi wavelength excitation can be used to obtain different emissions in visible and NIR regions. Under 380 and 980 nm excitation, the NASE-1000–1300 produces 1535 nm NIR emission, whereas green and red visible emissions are observed with 980 and 808 nm laser excitations. Under 980 nm laser excitation, the synthesis temperature dependent nepheline and carnegieite polymorphs emit intense red and green emission, respectively. Two-photon process is responsible for the green and red UC emissions of the NASE-1300. The NASE-1000-1300 produces intense red emission under 808 nm laser excitation. We believe that the NASE-1000–1300 could be a promising candidate for the photonic as well as biological applications.